Challenges and Resilience-Building: A Narrative Inquiry Study on a Mid-Career Chinese EFL Teacher - Xue, Lina (Frontiers in Psychology, 2021)
With a high rate of attrition and burnout of teachers as a global concern, teacher resilience has become a trendy topic in the research of their professional development as one of the pillars of positive psychology (positive character traits). However, the literature reveals that little research has been done on the mid-career teachers in the Chinese context, especially on how resilience may be nurtured, sustained, or eroded over time. Focusing on a mid-career EFL female teacher (the author) in China as a case study, this longitudinal self-reflective study employs a narrative inquiry to investigate the challenges that the experienced teacher was encountered with and to depict her trajectories of resilience-building by fleshing out the interaction between challenges, resources, and coping strategies in her three different scenarios. “Hard data”, such as teaching journals, reflective field notes, and messages with students were collected and analyzed inductively by using thematic analysis, and “soft data”, like memory was also referred to. The findings unfolded challenges confronting the experienced teacher peculiar to the Chinese context and charted a detailed bumpy journey of resilience building in three phases, accompanied by her growing emotional, intellectual, and psychological capacities. Implications are drawn out for teacher resilience building, school leaders, and policymakers.